Care of the e-sports athlete - Law, A.; Ho, G.; Moore, M. (Current Sports Medicine Reports, 2023)
The growth of electronic sports (esports), or competitive video gaming, in recent years has led to an increasing number of players seeking care for injuries and injury prevention associated with esports. In addition, the increase of esports players seeking care from health care professionals leads to a heightened awareness about the role of health and lifestyle in esports performance.